Is the Informal Sector Constrained from the Demand Side? : Evidence for Six West African Capitals - Bohme, Marcus; Thiele, Rainer (World Bank, Washington, DC, 2017)
Employing a unique dataset that covers households from six West African capitals, this paper provides new evidence on the demand for informal sector products and services. Authors first investigate whether demand linkages exist between formal and informal products and distribution channels. In a second step, authors estimate demand elasticity's based on Engel curves. Authors find strong demand-side linkages between the formal and informal sector, with the exception that informal goods are hardly bought through formal distribution channels. The estimated demand elasticity's tend to show that rising incomes are associated with a lower propensity to consume informal sector goods and to use informal distribution channels.